Evaluation of Medium Voltage Network for Propagation of Supraharmonics Resonance - Shimi Sudha Letha; Angela Espin Delgado; Sarah K. Rönnberg; Math H. J. Bollen (Energies, 2021)
Power converters with high switching frequency used to integrate renewable power sources to medium and low voltage networks are sources of emission in the supraharmonic range (2 to 150 kHz). When such converters are connected to a medium voltage (MV) network these supraharmonics propagate through the MV network and can impact network and customer equipment over a wide range. This paper evaluates an existing Swedish MV electrical network and studies the pattern of supraharmonic resonance and the propagation of supraharmonics. The MV network consists of eight feeders including a small wind farm. Simulations reveal that, the bigger the MV network, the more resonant frequencies, but also the lower the amplitude of the resonance peaks in the driving point impedance. It was also identified that for short feeders as length increases, the magnitude of the transfer impedance at supraharmonic frequency decreases. For further increment in feeder length, the magnitude increases or becomes almost constant. For very long feeders, the transfer impedance further starts decreasing. The eight feeders in the network under study are similar but show completely different impedance versus frequency characteristics. Measurements at the MV side of the wind farm show time varying emissions in the supraharmonic range during low power production. The impact of these emissions coupled with system resonance is examined.